2019
DOI: 10.1590/1981-52712015v43n2rb20180158
|View full text |Cite
|
Sign up to set email alerts
|

Fatores que Influenciam a Escolha da Especialização Médica pelos Estudantes de Medicina em uma Instituição de Ensino de Curitiba (PR)

Abstract: RESUMO A escolha da especialidade médica é de suma importância para o estudante de Medicina, uma vez que representa a escolha da sua prática diária. Embora a realização acadêmica, considerações financeiras e preferências de estilo de vida influenciem a escolha, os aspectos intrapessoais têm impacto na decisão do médico. Objetivos Avaliar os principais fatores que influenciam o acadêmico de Medicina na escolha da especialidade médica e identificar as áreas de atuação preferidas pelos estudantes dos quatro pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 6 publications
(6 reference statements)
0
7
0
8
Order By: Relevance
“…Moreover, most participants reported having undergone the selection process for admission to Internal Medicine Residency soon after graduation, which shows the tendency of early specialization of Brazilian physicians 15 , which sometimes occurs due to personal or social pressure 3 . Another factor found in the present study is that the minority of the participants has children, which may corroborate the young age at which medical specialization has been taking place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most participants reported having undergone the selection process for admission to Internal Medicine Residency soon after graduation, which shows the tendency of early specialization of Brazilian physicians 15 , which sometimes occurs due to personal or social pressure 3 . Another factor found in the present study is that the minority of the participants has children, which may corroborate the young age at which medical specialization has been taking place.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of medical specialty usually begins in the first semesters of undergraduate school and may change throughout the course and professional career. Previous studies have shown that it depends on multiple variables, such as financial return, possibility of division between work and free time, broader or more specific knowledge, influence of medical relatives and/or professors and affinity with the specialty 3 . Some studies in the international literature have discussed the reasons for the clinician to choose to subspecialize.…”
Section: Introductionmentioning
confidence: 99%
“…A escolha da especialidade médica começa, geralmente, nos primeiros semestres da graduação e pode sofrer mudanças ao longo do curso e da carreira profissional, tendo sido verificado, em estudos anteriores, que depende de múltiplas variáveis, como retorno financeiro, possibilidade de divisão entre trabalho e tempo livre, conhecimento mais amplo ou mais específico, influência de parentes médicos e/ou professores, e afinidade com a especialidade 3 .…”
Section: Introductionunclassified
“…Outrossim, a maioria dos participantes relatou ter realizado o processo seletivo para ingresso na residência em clínica médica logo após a graduação, o que mostra a tendência de especialização precoce do médico brasileiro 15 , aspecto decorrente, por vezes, de pressão própria ou social 3 . Outro dado encontrado em nosso estudo refere-se ao fato de a minoria ter filhos, o que pode corroborar a premissa de que uma população mais jovem opta pela especialização médica.…”
unclassified
“…Métodos: Se realizó un estudio descriptivo de corte transversal con estudiantes de prácticas médicas en la región sureste de Pará, utilizando un cuestionario en línea semiestructurado compuesto de datos sociodemográficos, perfil profesional, intención de asistir a residencia médica, especialidad futura y su intención de trabajar en la región. Resultados: Los 33 estudiantes con matrícula efectiva participaron en un internado en el sureste de Pará, con un ligero predominio de varones (51,5%) y una edad promedio de 26, 16. La especialidad favorita era la cirugía general, sin predominio de géneros, seguida de clínica médica y pediatría.…”
unclassified